2014
DOI: 10.1007/s11010-014-2201-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding and cytotoxic efficacy studies of organorhenium pentylcarbonate compounds

Abstract: Seven organorhenium pentylcarbonate compounds (PC1-PC7) have been synthesized. DNA-binding studies of the PC-series compounds using electronic spectroscopy and gel electrophoresis suggest that the compounds presumably bind to DNA in an intercalative mode. The intrinsic binding constants for PC4, PC6, and PC7 were found to be 1.6 × 10(4), 3.9 × 10(4), and 4.2 × 10(4) M(-1), respectively. The X-ray structure determinations and density functional theory calculations indicate that the polypyridyl ligands in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The UV titrations of PC1 were reported previously [ 17 ]. The UV titrations of RAC9 were carried out in a similar manner.…”
Section: Methodsmentioning
confidence: 99%
“…The UV titrations of PC1 were reported previously [ 17 ]. The UV titrations of RAC9 were carried out in a similar manner.…”
Section: Methodsmentioning
confidence: 99%
“…The selectivity of Re compounds for cancer cell lines is one of the main advantages over other organometallic drugs such as platinum compounds that suffer from strong side effects. For example, pentylcarbonato Re(CO) 3 compounds induced significant cytotoxic effects at the dose of 10 M for an exposure time of 48h in HTB-12 human astrocytoma brain cancer cells but not against CRL-2005 rat astrocyte normal brain cells [78]. Re(CO) 3 acetylsalicylato complexes showed a very selective cytotoxicity on HTB-12 human astrocytoma brain cancer cell lines and glioblastoma multiforme D54 cell lines versus rat normal brain astrocyte cells [77].…”
Section: Selectivity Of Rhenium Compounds For Cancer Cell Linesmentioning
confidence: 99%
“…The UV titration of these complexes showed that their absorbance decreased with addition of DNA without any red shift suggesting that these complexes did not follow intercalation mechanism but were more likely to bind to the minor grooves of the DNA double helix [77]. On the other hand, the structurally similar Re(CO 3 ) pentylcarbonato complexes in which each Re atom was tethered to a nearly planar polypyridyl aromatic ligand, were found to bind through an intercalation mechanism as evidenced by X-ray structure determinations and DFT calculations [78].…”
Section: Dna Effects Of Re Complexesmentioning
confidence: 99%
“…The other alternative complexes have at least one direct, covalent metal-carbon bond, having structural variety, diverse stereochemistry, provide control over major kinetic properties, kinetically stable, usually uncharged, and having low oxidation state of metal atom, so they can be used as ideal candidates for anticancer candidates [1][2][3][4]. Some examples are: metallocenes [5][6][7][8][9], organometallic ruthenium half-sandwich complexes [10][11][12][13][14], organometallic osmium half-sandwich complexes [15][16][17], organometallic iridium and rhodium complexes [18][19][20][21], rhenium organometallics [22][23][24], ruthenium, osmium, iridium, and platinum organometallics as scaffolds for protein kinase inhibitors, metal NHC complexes [25,26], and metal carbonyl complexes [27,28].…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…The remedy is now to search for new compounds with new mode of action to overcome the resistant strains. This can be done by either the organic derivatization of old drugs or completely new organometallic drugs, for example, new tamoxifen [19][20][21]29], platensimycin [22][23][24], etc.…”
Section: Antibacterial Agentsmentioning
confidence: 99%